FREQUENCY OF HIGH DEGREE ATRIOVENTRICULAR BLOCK IN PATIENTS WITH ACUTE ANTERIOR WALL MYOCARDIAL INFARCTION - DAR , WA; ULLAH , N; QURESHI , AE; FAROOQ , U; ANUM , H; SAJJAD , M (Biological and Clinical Sciences Research Journal, 2023)
Atrioventricular (AV) block is an AV conduction disorder that can manifest in various settings, with varying symptomaticity and severity. Complications of acute ST-elevation myocardial infarction (STEMI) as AV blocks are often observed. The first degree of atrioventricular block is the most common and requires no treatment. The second-degree block is sub-classified in Mobitz type I and Mobitz type II. This study aimed to determine the frequency of high-degree atrioventricular block in acute anterior wall myocardial infarction cases. The current cross-sectional analysis was conducted at the Department of Cardiology, Rehmat-ul-Lil-Alameen Institute of Cardiology, Lahore, from 19-02-2021 to 18-08-2021. A total of 311 patients were enrolled in the study. Cases underwent an electrocardiogram, and high degree AV Block was labeled per operational definitions. The results were noted and recorded on the same proforma. The overall mean age of the patients was 55.6±8.4 years. Gender distribution of patients shows a higher frequency of 57.9% males compared to 42.1% females with a female-to-male ratio of 1:1.4. High degree of atrioventricular block was found among 5.8% of the total patients. Around 5.8% of AWMI patients presented with high-grade AV block in this study are in-concomitant with other studies. No association of risk factors (p-value >0.05) was presented regarding age, gender, DM, hypertension, dyslipidemia, family history of CAD, and smoking in this study.